BS EN IEC 62841-4-7 AMDAA. Electric motor-operated hand-held tools, transportable tools and lawn and garden machinery. Safety. Part 4-7. Particular requirements for pedestrian controlled walk-behind lawn scarifiers and aerators (1st July 2021) - British Standards Institution,
No abstract available